PENGAWASAN OPERASIONAL PANTI ASUHAN DI KOTA PEKANBARU - Putri Rahmadani; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The purpose of this study is to determine the extent of operational supervision of orphanages in Pekanbaru City and to find out what factors are hampering the operational supervision of orphanages in Pekanbaru City. The problem of this research is that there are still many orphanages that do not provide monthly activity reports to the Pekanbaru City Social Service, the lack of supervision of the Pekanbaru City Social Service on the existence of orphanages in Pekanbaru City. The selection of informants uses Purposive Sampling techniques with data collection techniques including: observation, interviews and documentation. The results of this study can be seen that the Oversight of Orphanage Operations in Pekanbaru City is not optimal. Operational oversight of orphanages in Pekanbaru City has not run optimally, this is because there are still orphanage owners who have more than one orphanage by using one name and supervision schedule should be done once a month but, in fact Pekanbaru City Social Service is sometimes not go down to the institution to conduct surveillance for reasons that are not clear. In addition, the deadline set by the Office is too close or fast, that is, once a month the orphanage must report the activities of the orphanage to the Office, consequently making the orphanage owner in Pekanbaru feel overwhelmed, therefore the orphanage does not fulfill its obligation to report activities every month to the Social Service City of Pekanbaru. Keyword: Supervision, Operations, Orphanages